MOTIVASI BELAJAR DAN BIMBINGAN AKADEMIK MENENTUKAN PRESTASI BELAJAR - Yanita Trisetiyaningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Academic or school achievement is expressed in a variety of indicators, in aform of grades, GPA, etc. studies. Experts say that the success of learning is influenced bymany internal or external factors of individuals. Motivation is one of the internal factors that influence the success / achievement of one's learning. In addition to motivation, learning processes result in mutual interaction of various factors, namely students, teachers or facilitators (teachers, lecturers, or tutors), methods of teaching and learning aids, and materials studied. Objective: To determine the relationship of academic motivation and guidance to nursing students’ academic achievement in A. Yani Health School (STIKES A. Yani), Yogyakarta. Methods: This was a quantitative research with a non-experimental approach and a crosssectional design. The retrospective method was for academic achievement variable and the prospective method was for motivation and academic guidance variables. A method of Focus Discussion Group (FGD) was also applied. Subjects were nursing students, minimally sittingin the second semester. Statistical tests used Spearman Rank and Linear Regression. Results:The analysis results of Spearman Rank correlation test between learning motivation and academic achievement earned a value of p (0.000) <0.05 with the correlation (r) of 0.78.The analysis results of Rank Spearman correlation test between academic guidance and academic achievement obtained p value (0.000) <0.05 with a correlation coefficient (r) of0.437.In addition, the analysis results of linear regression correlation on the relationship of learning motivation and academic guidance to academic achievement obtained rho value (0.458) > rho table (0.175). Conclusion: There was a relationship of learning motivation and academic guidance to nursing students’ academic achievement in STIKES A. Yani Yogyakarta. Keywords: motivation, academic guidance, academic achievement